2022
DOI: 10.3390/ijerph19159059
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cancer in Pre-Menopausal Women and Younger: Risk Factors and Outcome

Abstract: Endometrial cancer is the sixth most common malignancy in women, and it is known to be a disease among postmenopausal women, but there is rising in the number of endometrial cancers among premenopausal women. This study aims to determine the clinical characteristic, risk factors, outcomes, and survival in pre and postmenopausal women with endometrial cancer in Malaysia. A retrospective study was conducted in Hospital Melaka that involved all women who were diagnosed with endometrial cancer in Hospital Melaka f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
(52 reference statements)
3
9
0
Order By: Relevance
“…In recent years, the role of fertility changes in increasing the incidence of EC has been the focus of many researchers. Accordingly, early menarche, late menopause, increased number of menstrual cycles and nulliparity increase the risk of EC 4,6,34 . In this regard, results of a study showed that obesity, nulliparity, and early menarche are risk factors for EC in premenopausal women 6 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, the role of fertility changes in increasing the incidence of EC has been the focus of many researchers. Accordingly, early menarche, late menopause, increased number of menstrual cycles and nulliparity increase the risk of EC 4,6,34 . In this regard, results of a study showed that obesity, nulliparity, and early menarche are risk factors for EC in premenopausal women 6 …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, early menarche, late menopause, increased number of menstrual cycles and nulliparity increase the risk of EC. 4,6,34 In this regard, results of a study showed that obesity, nulliparity, and early menarche are risk factors for EC in premenopausal women. 6 SDI is associated with lifestyle, dietary patterns, and disease risk factors.…”
Section: According To Thementioning
confidence: 99%
See 3 more Smart Citations